Density‐Controlled Metal Nanocluster with Modulated Surface for pH‐Universal and Robust Water Splitting (Adv. Funct. Mater. 12/2023). (16th March 2023) - Shao, Xiaodong; Liang, Mengfang; Kim, Min Gyu; Ajmal, Sara; Kumar, Ashwani; Liu, Xinghui; Jung, Hyun Seung; Jin, Haiyan; Cao, Fengliang; Yu, Jianmin; Tran, Kim My; Ko, Hyun; et al.
Abstract : Density‐Controlled Metal Nanocluster In article number 2211192, Hyoyoung Lee and co‐workers report a simple and effective strategy for preparing a series of density‐controlled and surface‐modulated metal nanoclusters with the assistance of a N‐rich and size‐limited covalent organic polymer. The prepared Ir nanoclusters show better HER and OER performances than commercial Pt/C and Ir/C, respectively.